Anatomy: An Opportunity for South African Health Science Students to Discuss Their Emotional Responses to Human Remains in the Laboratory - Carol A. Hartmann; Erin F. Hutchinson; Beverley Kramer (MDPI AG, 2022)
Human dissection remains a cornerstone of the anatomy learning experience. However, the emotional response of students to the use of human remains for learning is influenced by a number of factors and is not always positive. Therefore, this study explored the students' emotional response to and factors affecting their perceptions of the use of human remains for learning anatomy in a South African context. Four hundred and eighty of the 1538 health sciences students enrolled in human anatomy courses at the University of the Witwatersrand, South Africa during 2016 and 2017, completed a voluntary survey. The survey included closed and open-ended questions on students' emotional responses, coping mechanisms and the factors that affected their perceptions of the use of human remains and dissection. Overall, the students had a positive emotional response. Their perceptions of dissection were affected in positive and negative ways by their religious and cultural beliefs. Feelings of gratitude and respect toward the cadaver were informed by belief systems. However, anxiety was caused by the delay of accepted sociocultural burial practices. Peer discussions were the preferred coping method, which may provide an approach for students to discuss how their beliefs influence their dissection experience.